2008
DOI: 10.1175/2008jpo3853.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiating Instability of a Meridional Boundary Current

Abstract: A linear stability analysis of a meridional boundary current on the beta plane is presented. The boundary current is idealized as a constant-speed meridional jet adjacent to a semi-infinite motionless far field. The far-field region can be situated either on the eastern or the western side of the jet, representing a western or an eastern boundary current, respectively. It is found that when unstable, the meridional boundary current generates temporally growing propagating waves that transport energy away from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 7 publications
5
58
3
Order By: Relevance
“…The lateral eddy heat flux terms are concentrated in the eastern basin, where the vertical shear in the meridional velocity is the largest, but the perturbations are able to penetrate westward all the way to the western boundary. This is similar to the radiation from unstable meridional eastern boundary currents recently discussed by Hristova et al [2008].…”
Section: Dynamics Of the Moc Variabilitysupporting
confidence: 84%
“…The lateral eddy heat flux terms are concentrated in the eastern basin, where the vertical shear in the meridional velocity is the largest, but the perturbations are able to penetrate westward all the way to the western boundary. This is similar to the radiation from unstable meridional eastern boundary currents recently discussed by Hristova et al [2008].…”
Section: Dynamics Of the Moc Variabilitysupporting
confidence: 84%
“…Afanasyev et al, 2011), radiating instabilities of the eastern boundary current (e.g. Hristova et al, 2008;Wang et al, 2012), stationary Rossby waves (e.g. Maximenko et al, 2008), and the nonlinear self-interactions of the linear eigenmodes (e.g.…”
Section: Banded Structures In the Low-frequency Eddy Fieldmentioning
confidence: 99%
“…We term this hypothesis the "vortex-propagation mechanism". Other formation mechanisms include, but are not limited to, stationary Rossby waves (Maximenko et al, 2008), beta plumes (Afanasyev et al, 2011), radiating instabilities of the eastern boundary current (Hristova et al, 2008;Wang et al, 2012), and the nonlinear self-interactions of the linear eigenmodes (Berloff, 2005;Berloff et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Alternative hypotheses based on three-dimensional models have been proposed to explain mechanisms of QZJ generation; see Hristova et al (2008), Berloff et al (2009Berloff et al ( , 2011, Tanaka and Akitomo (2010), Wang et al (2012) and Qiu at al. (2013), among others.…”
Section: Introductionmentioning
confidence: 99%
“…(2013), among others. For example, Hristova et al (2008) hypothesized that QZJs observed in the eastern region of subtropical gyres may be related to radiating instabilities of eastern boundary currents. Connaugton et al (2010) have suggested using a modulational instability concept for explanation of quasi-zonal jets observed in the ocean and atmosphere.…”
Section: Introductionmentioning
confidence: 99%